2019
DOI: 10.1111/jonm.12779
|View full text |Cite
|
Sign up to set email alerts
|

Effects of workplace cyberbullying on nurses' symptom experience and turnover intention

Abstract: Aims The purpose of this study was to investigate the effect of workplace cyberbullying on nurses' symptom experience and turnover intention. Background While face‐to‐face workplace bullying occurs frequently in nursing organisations, workplace cyberbullying has rarely been studied. Method This is a cross‐sectional descriptive study using self‐reporting surveys of 249 nurses from 20 hospitals. Results The prevalence of workplace cyberbullying was 8%, and the mean was 1.11 ± 0.31. Factors influencing symptom ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 30 publications
2
46
1
Order By: Relevance
“…Turnover intention is a typical variable measured in tandem with other cross-sectional data on disruptive behaviors and work environment. [42][43][44] Turnover intention may be linked to actual rates though causality cannot be established. In this study, intent to stay was very high with 80% planning to remain in their position.…”
Section: Discussionmentioning
confidence: 99%
“…Turnover intention is a typical variable measured in tandem with other cross-sectional data on disruptive behaviors and work environment. [42][43][44] Turnover intention may be linked to actual rates though causality cannot be established. In this study, intent to stay was very high with 80% planning to remain in their position.…”
Section: Discussionmentioning
confidence: 99%
“…The three themes D'Souza et al identified as cyberbullying behaviors as (1) cyber‐specific features that amplify harm, (2) the role of context, and (3) work environment factors, which facilitate cyberbullying behaviors 11 . A cross‐sectional study using survey methods by Park and Choi 26 found that workplace cyberbullying was prevalent among 8% of Korean nurses respondents. Workplace cyberbullying was significantly correlated with perceived organizational support, turnover intention, and symptom experience 26 .…”
Section: Definitions and Uses Of Conceptmentioning
confidence: 99%
“…A cross‐sectional study using survey methods by Park and Choi 26 found that workplace cyberbullying was prevalent among 8% of Korean nurses respondents. Workplace cyberbullying was significantly correlated with perceived organizational support, turnover intention, and symptom experience 26 . In another study by Choi and Park, 27 the state of face‐to‐face bullying or cyberbullying in a Korean hospital were explored as they related to workplace culture.…”
Section: Definitions and Uses Of Conceptmentioning
confidence: 99%
See 2 more Smart Citations